Serum Levels Evaluation of Heat Shock Protein70 during Gestation and Fetal Birth Weight in Asthmatic Women of Thi-QAR Province, Iraq - Salman, Ali Naeem (Al-Nahrain Journal of Science, 2018)
Asthma is a multifactorial inflammatory disease of the upper airways and it`s one of the most common diseases complicating pregnancy and represents a risk factor for several maternal and perinatal complications. The natural history of asthma is known to change in pregnancy, but very few data are available in the terms of pathomechanism of this change during gestation. Circulating heat shock protein 70 (Hsp70) levels are decreased in healthy pregnancy, which might reflect physiological immunotolerance. The aim of our study was to determine the serum levels of Hsp70 in asthmatic women during gestation. Fifty pregnant women with bronchial asthma and 50 healthy pregnant women matched for maternal and gestational age were involved in this case-control study. Serum Hsp70 levels were measured using the Bioassay ELISA Kit. In asthmatic pregnant women, an increase of serum Hsp70 levels was observed compared to healthy pregnant women (median18–75 percentile): 0.46 ng/ml versus 0.16 ng/ml p0.05). A statistically significant negative correlation between maternal age and serum Hsp70 concentrations (p